Optimum tuning parameters of tuned mass dampers for vibration control of irregular highrise building structures - Soto, Mariantonieta Gutierrez; Adeli, Hojjat (Journal of Civil Engineering and Management, 2014)
Tall buildings have become increasingly one-of-a-kind signature structures that are often irregular in plan and elevation with complicated dynamic behavior. Vibration control of irregular highrise building structures using a recently developed tuned mass dampers (TMD), the bidirectional TMD (BTMD), is investigated. A key issue for effective implementation of a TMD is the determination of their tuning parameters. Eight different sets of equations for tuning the parameters of TMDs are investigated using a 5-story building with plan and elevation irregularity, and a 15-story and a 20-story building with plan irregularity subjected to seismic loading. Appropriate equations are recommended for building structures with a fundamental period of vibrations of greater than one second.